Analysis of Microplastic Containment in Coral Grouper (Cephalopholis miniata) and Brown-Marbled Grouper (Epinephelus fuscogattatus) Grown on the Station of Baguk Island, Singkil Aceh - Inayah, Safa Aulafi; Nufus, Hayatun; Rizal, Muhammad; Oktavinanda, Giovanni; Astuti, Rika (Journal of Coastal and Ocean Sciences, 2024)
Baguk Island is one of several islands in the Aceh Singkil Regency. This water area is included in a coastal ecosystem widely used for various human activities, such as sea transportation routes; these activities can increase domestic and anthropogenic waste, including microplastics. The study aimed to determine the type and amount of microplastic content in coral groupers (Cephalopholis miniata) and Brown-marbled grouper (Epinephelus fuscogattatus), fish often consumed by the community. This research was conducted in August-November 2023 in the tangkahan of Baguk Island village using quantitative methods where data collection was carried out through field surveys and laboratory experiments based on the NOAA (National Oceanic and Atmospheric Administration) method but with several differences, namely the number of samples and the addition of hydrogen peroxide (H2O2) solution. The results of the identification of this study found as many as three types of microplastics in coral grouper fish, namely fragment, film and fiber types and four types of microplastics in Brown-marbled grouper fish with fragment, film, fiber and granule types